Analisis manajemen risiko pada zona integritas di Balai Pengembangan Kompetensi PUPR Wilayah VI Surabaya - Emilda, Dwi Putri; Amiruddin, Amiruddin; Syamsuddin, Syamsuddin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine the risk management process in the integrity zone at the PUPR Region VI Competency Development Center Surabaya and the factors that influence it. This research is a qualitative research with a case study approach. Data collection was carried out through interviews with seven informants selected using purposive sampling. The results showed that the risk management process in the integrity zone at the PUPR Region VI Competency Development Center in Surabaya was at the risk defined stage. This shows that strategies and regulations already exist and are communicated and risk appetite has been established, but risk identification is still limited. Factors that influence the risk management process in the integrity zone at the PUPR Region VI Competency Development Center in Surabaya are communication, understanding of risk management, work culture, leadership commitment, motivation and consistency.